KARAKTERISASI MORFOLOGI PISANG BATU (Musa balbisiana Colla) DI KABUPATEN KUANTAN SINGINGI - Slamet Prayogi; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Musa balbisiana Colla in Kuantan Singingi Regency can survive from the disease which causes banana in many other areas disappeared. Currently, there is no information about the diversity of M. Balbisiana from Kuantan Singingi. The purposesof this study were to record, to characterize, and to measure the diversity of M. balbisiana from Kuantan Singingi based on morphological characters. M. balbisiana Colla plants was sampled from three locations in Kuantan Singingi, they were Pangean, Cerenti, and Inuman. Morphological characters of M. balbisiana were analyzed using 88 characters. Analysis of UPGMA was conducted to find out the diversity of M.Balbisiana. We found six M.balbisiana cultivars, namely Aceh, Bungo, Kara, Jambi, Nipah, Beluluk. Similarity coefficient values between six banana cultivars ranged from 63%-89%. Cluster analysis based on 88 morphological characters of M. balbisianaproduced dendogram with 2 primary groups at percentage of similarity values of 66%.